Process control strategies for the gas phase synthesis of silicon nanoparticles - Gröschel, Michael; Koermer, Richard; Walther, Maximilian; Leugering, Günter; Peukert, Wolfgang (Chemical Engineering Science, 2012)
In this contribution the identification of new reaction conditions for the production of nearly monodisperse silicon nanoparticles via the pyrolysis of monosilane in a hot wall reactor is considered. For this purpose a full finite volume model has been combined with a state-of-the-art trust-region optimisation algorithm for process control. Verified against experimental data, specific process conditions are determined accomplishing a versatile range of prescribed product properties. The main achievement of the optimisation is the possibility to control the different mechanisms in the particle formation process by mainly adjusting the temperature profile. Due to a successful separation of the nucleation and growth process, significantly narrower particle size distributions are obtained. Moreover, the presented optimisation framework establishes rate constants based on measured data.

Towards a lifecycle oriented design of infrastructure by mathematical optimization - Kufner, Tobias; Leugering, Günter; Martin, Alexander; Medgenberg, J.; Schelbert, Jakob; Schewe, Lars; Stingl, Michael; Strohmeyer, Christoph; Walther, Maximilian (Optimization and Engineering, 2019)
Today’s infrastructures are mainly designed heuristically using state-of-the-art simulation software and engineering approaches. However, due to complexity, only part of the restrictions and costs that show up during the lifecycle can be taken into account. In this paper, we focus on a typical and important class of infrastructure problems, the design of high-pressure steam pipes in power plants, and describe a holistic approach taking all design, physical, and technical constraints and the costs over the full lifecycle into account. The problem leads to a large-scale mixed-integer optimization problem with partial differential equation (PDE) constraints which will be addressed hierarchically. The hierarchy consists of a combinatorial and a PDE-constrained optimization problem. The final design is evaluated with respect to damage, using beam models that are nonlinear with respect to kinematics as well as constitutive law. We demonstrate the success of our approach on a real-world instance from our industrial partner Bilfinger SE.<br
Keywords: Structural optimization; Lifecycle oriented design; Mixed integer nonlinear programming